Соціально-психологічні уявлення військовослужбовців про злочин і злочинця - Худавердова, А. О.; Khudaverdova, A. O. (Теоретичні і прикладні проблеми психології та соціальної роботи. – 2021. – № 3(56), т. 2. – С. 300-310, 2021)
Розкрито особливості соціальних уявлень про злочин та злочинця у групах військовослужбовців з різним правовим статусом (законослухняні і правопорушники). Наголошено, що існує протиріччя між нормативними вимогами до поведінки військовослужбовця у воєнний та мирний час. Зазначено, що перебування особи в умовах бойових дій протягом тривалого часу приводить до певних деформацій у сприйнятті людиною таких категорій як злочин, правопорушення, закон тощо. Соціальні уявлення містять інформацію, переконання, думки, образи, установки щодо об’єкта уявлення. Вони орієнтують і «виправдовують» поведінку індивідів, сприяють соціальним комунікаціям.

The aim of the work is to study the features of social perceptions of crime and the offender in groups of military service members with different legal status (law-abiding and offenders). It is emphasized that there is a contradiction between the regulatory requirements for the conduct of military personnel in wartime and peacetime. It is noted that the presence of a person in combat for a long time leads to certain distortions in human's perception of such categories as crime, offense, law and so on. Social representations contain information, beliefs, thoughts, images, attitudes about the object of representation. They guide and "justify" the behavior of individuals, promote social communication. Different experiences, group affiliation, activities - all this contributes to the formation of different ideas in individuals. Social ideas about crimes are complex systems consisting of a number of interdependent elements, their structure is not homogeneous, the degree of danger of crimes is not considered the same. The paper reveals the features of social perceptions of criminals and crimes in military service members who are law-conscious (first group) and military service members who have committed crimes (second group). It is shown that in the group of military personnel who have committed offenses, representations have a more complex and contradictory structure; and in the first group - law-abiding military service members - representations have a simpler form. In both groups, social perceptions are built around such categories as the type of crime (murder, theft, etc.), the negative personality traits of the offender and strong negative emotional reactions. Social perceptions of crime also include such a group as punishment. The nuclei of social ideas in each case are formed by different elements depending on the group. The subjects of the first group in their social ideas are more unambiguous, strict and tend to determine crime by the fact that a person is "bad". Most approve of the imposition of the death penalty. Offenders, on the contrary, are more humane, tend to determine crime by social difficulties, to believe in the possibility of correction. They are also characterized by the presence of such a construct as fear and a large number of references to legislation and regulations. In addition, military service members who have committed crimes tend to take the abstract position of the victim.

Раскрыты особенности социальных представлений о преступлении и преступнике в группах военнослужащих с разным правовым статусом (законопослушные и правонарушители). Отмечено, что существует противоречие между нормативными требованиями поведения военнослужащего в военное и мирное время. Подчеркнуто, что пребывание личности в условиях боевых действий в течение длительного времени приводит к определенным деформациям в восприятии человеком таких категорий как преступление, правонарушение, закон и т.п. Социальные представления содержат информацию, убеждения, мнения, образы, установки по объекту представления. Они ориентируют и «оправдывают» поведение индивидов, способствуют социальным коммуникациям.
Socio-psychological perceptions of military servants about crime and criminal
Худавердова, А. О. Соціально-психологічні уявлення військовослужбовців про злочин і злочинця / Худавердова А. О. // Теоретичні і прикладні проблеми психології та соціальної роботи. – 2021. – № 3(56), т. 2. – С. 300-310. - DOI: https://doi.org/10.33216/2219-2654-2021-56-3-2-300-310.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; військовослужбовці; military personnel; военнослужащие; соціальні уявлення; social ideas; социальные представления; поведінка; behavior; поведение; злочин; crime; преступление; злочинець; offender; преступник; жертва; victim; правопорушення; offense; правонарушение